Enhancing the Performance of CFRP Shear-Strengthened RC Beams Using “Ductile” Anchoring Devices - Hu, Zhiheng; Zhou, Xiaoqing; Guo, Menghuan; Huang, Xiaoxu; Hu, Biao (Frontiers in Materials, 2020)
Reinforced concrete (RC) beams that are shear-strengthened by externally bonded (EB) fiber reinforced polymer (FRP) often yield limited structural enhancement. This is due to the inherent weaknesses of EB-FRP strengthening, including the premature debonding of the FRP, its brittle rupture, and inadequate deformation capacity of the strengthening system. In this paper, two techniques of shear strengthening using U-wrapped carbon FRP (CFRP) and effective anchoring devices are proposed and tested with the aim of enhancing both the shear strength and the ductility of retrofitted RC beams. One of the techniques involves a hybrid-bonded (HB) CFRP system with adjustable normal pressure applied to the CFRP U-strips, and the other features the CFRP U-strips fastened by an H-type end anchor (EA). The main test variables of the former and latter shear-strengthening systems are normal pressures applied to the CFRP U-strips and the width of the deformation segment (or axial stiffness) of the H-type EA, respectively. The results indicate that both strengthening systems significantly enhanced the shear capacity and ductility of the strengthened RC beams. Compared with the control member, the increments in shear capacity were as high as 54.6% and 68.5% for beams retrofitted with the HB-FRP and the EA FRP systems, respectively, and their deflections at peak shear load increased by 43.9% and 84.1%, respectively. The shear failure modes were found to be related to the parameters used in both the HB-FRP and the EA FRP systems. The critical diagonal crack (CDC) inclination of all specimens was less than 45°, ranging from 38° to 44°. Both positive and negative shear interactions were observed between Vf and Vc plus Vs.